Factors associated with a clinically relevant reduction in menopausal symptoms of a standardized acupuncture approach for women with bothersome menopausal symptoms - Frans Boch Waldorff; Christine Winther Bang; Volkert Siersma; John Brodersen; Kamma Sundgaard Lund (BMC, 2021)
Abstract Background Little is known about factors associated with a clinically relevant reduction in menopausal symptoms through a brief acupuncture approach for women with moderate-to-severe menopausal symptoms. Methods Post hoc analysis of a randomized controlled trial where participants were allocated to early versus late standardized acupuncture. Both the early group and the late group are included in this study. The late group got an identical intervention parallel staged by 6 weeks. By means of the relative importance, the effect was evaluated for both early versus late women with a 6-week follow-up. We included four symptom subscales from the validated MenoScores Questionnaire: hot flushes, day and night sweats, general sweating, menopausal-specific sleeping problems, as well as an overall score, which is the sum of the four outcomes in the analysis. Results 67 women with moderate to severe menopausal symptoms were included of whom 52 (77.6%) experienced a clinically relevant reduction in any of the four surveyed symptom subscales or overall score. 48 (71.6%) women experienced a clinically relevant reduction in any of the vasomotor symptom subscales: hot flushes, day and night sweats, general sweating. Women with vocational education were most likely to experience improvement compared to women with higher education. Beyond education, other factors of some importance for a clinically relevant reduction were no alcohol consumption, two or more births and urinary incontinence. Conclusions Level of education was the most consistent factor associated with improvement. Beyond education, other factors of some importance were no alcohol consumption, two or more births and urinary incontinence. Trial registration This study was registered in ClinicalTrials.gov at April 21, 2016. The registration number is NCT02746497 .